2010
DOI: 10.1186/1757-7241-18-37
|View full text |Cite
|
Sign up to set email alerts
|

Current use of intraosseous infusion in Danish emergency departments: a cross-sectional study

Abstract: BackgroundIntraosseous infusion (IOI) is recommended when intravenous access cannot be readily established in both pediatric and adult resuscitation. We evaluated the current use of IOI in Danish emergency departments (EDs).MethodsAn online questionnaire was e-mailed to the Heads of Department of the twenty EDs currently established in Denmark. The questionnaire focused on the use of IOI in the EDs and included questions on frequency of use, training, equipment and attitudes towards IOI.ResultsWe received a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…While a UK survey, performed in 1996, found IO equipment in only 7% of emergency departments (ED), a 2009 survey in Denmark found that 95% of ED personnel knew about IO lines, but only 48% had received training [25][26]. In this latter study, an average of five IO lines were placed per month per ED surveyed.…”
Section: Discussionmentioning
confidence: 93%
“…While a UK survey, performed in 1996, found IO equipment in only 7% of emergency departments (ED), a 2009 survey in Denmark found that 95% of ED personnel knew about IO lines, but only 48% had received training [25][26]. In this latter study, an average of five IO lines were placed per month per ED surveyed.…”
Section: Discussionmentioning
confidence: 93%
“…(23) Molin et al (24) determined that the lack of training and knowledge of the technique influenced the rate of its use in hospitals in Denmark.…”
Section: Resultsmentioning
confidence: 99%
“…Cook Medical Inc, Bloomington, IN, USA A manual device that is likely to be familiar to many emergency nurses (Fenwick, 2010). Although this device has been used for adults (Brenner et al, 2008;Molin et al, 2010), product information from Cook Medical (2014) would indicate that it is recommended for use in paediatric emergencies. Jamshidi ® needle CareFusion, San Diego, CA, USA…”
Section: Cook Needlementioning
confidence: 99%